Reproducibility of AMPLICOR enterovirus PCR test results. - Rotbart, H A (1997)
The reproducibility of AMPLICOR enterovirus PCR test results was determined with clinical samples of cerebrospinal fluid, serum, urine, and throat and rectal swabs. Among 608 samples from which duplicate aliquots were run simultaneously, only seven pairs gave discordant results. Among 104 samples from which duplicate aliquots were run in separate assays, no discordance was seen. Overall, the reproducibility of test kit results was 99% (705 of 712).